ANALYSIS OF THE EFFECT OF NET PROFIT MARGIN, RETURN ON ASSETS AND RETURN ON EQUITY ON STOCK PRICE (Case Study on Consumption Industrial Sector Companies Listed in Indonesian Sharia Stock Index at Indonesia Stock Exchange in 2016) - Wartoyo Hadi (The Management Journal of Binaniaga, 2018)
This study aims to analyze the effect of Net Profit Margin, Return On Assets, and Return On Equity on Stock Price of consumption industrial sector companies listed in Indonesian Sharia Stock Index at Indonesia Stock Exchange. The method of growth analysis which used is quantitative descriptive method. Whereas to find out the effect of Net Profit Margin, Return On Assets, and Return On Equity for Stock Price partially or simultaneously use descriptive method and multiple linear regression analysis technique. The study results that obtained show that partially Net Profit Margin and Return On Assets do not affect stock price, whereas Return On Equity effects on stock price. Simultaneously Net Profit Margin, Return On Assets, and Return On Equity affect stock prices. Key words: Net Profit Margin, Return On Assets, Return On Equity, and Stock Price